Periprocedural Management During Stroke Thrombectomy. (16th November 2021) - Simonsen, Claus Z.; Bösel, Julian; Rasmussen, Mads
Abstract : Purpose of Review: Endovascular therapy (EVT) for acute ischemic stroke caused by large vessel occlusion is a powerful and evidence-based tool to achieve reperfusion and results in improved neurologic outcome. Focus has now shifted toward optimizing the procedure. We reviewed the relevant current literature on periprocedural stroke care such as pretreatment with IV tissue plasminogen activator (tPA), choice of anesthesia, ventilation strategy, and blood pressure management. Recent Findings: IV tPA should not be withheld in a patients with stroke eligible for EVT. A meta-analysis of randomized trials on general anesthesia (GA) vs procedural sedation has shown better neurologic outcomes with protocol-based GA in centers with dedicated neuroanesthesia teams. There are no data from randomized trials on blood pressure control, but according to available evidence, systolic blood pressure should probably be held at >140 mm Hg during the procedure and <160 mm Hg after reperfusion. In ventilated patients, extreme deviations from normoxemia and normocapnia should be avoided. Summary: Periprocedural care influences the outcome after EVT for large vessel ischemic stroke. More evidence from prospective ongoing and future studies is urgently needed to identify its optimization.